PENGARUH METODE BERCERITA DENGAN MEDIA BIGBOOK TERHADAP KEMAMPUAN MENYIMAK ANAK USIA 5-6 TAHUN DI SPS AZ-ZAHRA KELURAHAN SUKAMULIA KECAMATAN SAIL KOTA PEKANBARU - Endang Ratna Susilawati; Daviq Chairilsyah; Hukmi Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstarck : This study aims to determine how much influence the Storytelling method using Bigbook for listening skills of children aged 5-6 years in the SPS Az-Zahra Village Sukamulia District of Sail Pekanbaru. This study consists of two variables: Bigbook and Observing Capabilities. The hypothesis of this study are as follows: Method Tells the Big Book Media can improve the ability of Listening Childhood 5-6 Years On SPS Az-Zahra, Village Sukamulia, District Sail, Pekanbaru ". The study involved 15 subjects ie 5-6 years old. Methods of data collection in this study using experimental. The data analysis technique used in this study is a partial correlation techniques using facilities assistance program SPSS 17.0 for windos.The results showed there was a significant positive relationship between the Storytelling method using Bigbook for listening skills of children aged 5-6 years in the SPS Az-Zahra Village Sukamulia District of Sail Pekanbaru. Based on the results of test results the average difference in the ability to listen to children before treated storytelling with book and after the big media treated book tells the big media, the value t = 89.154 while ttabel to df = 14 and a confidence level of 95% was obtained 2,145. So thitung (89.154)> t table (2.145) with a value signinifikansi 0, 000 <α (0.05), then H0 is rejected and Ha accepted. Listening skills of children aged 5-6 years in SPS Az-Zahra, Village Sukamulia, District Sail, Pekanbaru, after application of the media big book of 86.7% to the category of Emerging Very Good (BSB).Keywords: Bigbook, Listening Capabilities